PAHs, nitro‐PAHs, hopanes, and steranes in lake trout from Lake Michigan - Huang, Lei; Chernyak, Sergei M.; Batterman, Stuart A. (Environmental Toxicology and Chemistry, 2014)
The present study examines concentrations and risks of polycyclic aromatic hydrocarbons (PAHs), nitro‐PAHs (NPAHs), steranes, and hopanes in lake trout collected in Lake Michigan. A total of 74 fish were collected in 2 seasons at 3 offshore sites. The total PAH concentration (Σ 9 PAH) in whole fish ranged from 223 pg/g to 1704 pg/g wet weight, and PAH concentrations and profiles were similar across season, site, and sex. The total NPAH (Σ 9 NPAH) concentrations ranged from 0.2 pg/g to 31 pg/g wet weight, and carcinogenic compounds, including 1‐nitropyrene and 6‐nitrochrysene, were detected. In the fall, NPAH concentrations were low at the Illinois site (0.2–0.5 pg/g wet wt), and site profiles differed considerably; in the spring, concentrations and profiles were similar across sites, possibly reflecting changes in fish behavior. In the fall, the total sterane (Σ 5 Sterane) and total hopane (Σ 2 Hopane) levels reached 808 pg/g and 141 pg/g wet weight, respectively, but concentrations in the spring were 10 times lower. Concentrations in eggs (fall only) were on the same order of magnitude as those in whole fish. These results demonstrate the presence of target semivolatile organic compounds in a top predator fish, and are consistent with PAH biodilution observed previously. Using the available toxicity information for PAHs and NPAHs, the expected cancer risk from consumption of lake trout sampled are low. However, NPAHs contributed a significant portion of the toxic equivalencies in some samples. The present study provides the first measurements of NPAHs in freshwater fish, and results suggest that additional assessment is warranted. Environ Toxicol Chem 2014;33:1792–1801 . © 2014 SETAC Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/108087/1/etc2620.pdf